ANATOMI DAN IDENTIFIKASI SEPULUH JENIS KAYU DARI SULAWESI UTARA - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Gross and anatomical features of ten wood species from North Sulawesi were observed and described. Two of them hove light colour and considerable hard, and therefore recommended for ramin substitute. They are Pangium edule and Neonauclea sp.For identification purposes several important features were noted: oil cell in Elmerillia, perforation plate scalariform in Elmerillia and Laplacea, vertical septum in axial parenchima strand of Serianthes, fiber septate in Pangium, Aglaia and Desoxylum.Serianthes minahassae contain fiber with best quality. It is therefore recommended for pulpwood.